2015
DOI: 10.1080/02827581.2015.1048717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic treatment on seed germination of loblolly pine (Pinus taedaL.)

Abstract: Based on preliminary experiments, the speed of germination (SG) was in general increased for Pinus taeda L. seeds treated with a static magnetic field (B = 150 mT) for 10, 30 and 60 min. Negative impact was obtained for seeds treated with SMF for 24 h and 48 h. Mean germination time (MGT), the SG, and time required to obtain 10%, 25%, 50%, 75%, and 90% of seeds to germinate (T 10 -T 90 ) were calculated. Results showed a reduction of the MGT and T 10 -T 90 for seeds treated with SMF for 10, 30, and 60 min; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Several seed improvement methods have been employed to enhance seed vigor, including chemical treatments (chemicals, fungicides, and hormones) [Zehra et al, ; Zhao and Jiang, ] and physical treatments (ultrasonic scratching, electric field treatment, magnetic treatment, ion beam scratching, etc.) [Goussous et al, ; Xu et al, ; Shi et al, ; Yao and Shen, ]. Chemical methods are usually labor‐intensive and expensive due to large amounts of chemical consumption; even worse, residual chemicals on the seed coat surface could contribute to soil pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several seed improvement methods have been employed to enhance seed vigor, including chemical treatments (chemicals, fungicides, and hormones) [Zehra et al, ; Zhao and Jiang, ] and physical treatments (ultrasonic scratching, electric field treatment, magnetic treatment, ion beam scratching, etc.) [Goussous et al, ; Xu et al, ; Shi et al, ; Yao and Shen, ]. Chemical methods are usually labor‐intensive and expensive due to large amounts of chemical consumption; even worse, residual chemicals on the seed coat surface could contribute to soil pollution.…”
Section: Introductionmentioning
confidence: 99%
“…As physical methods, ultrasonic scratching and ion beam scratching could improve seed vigor, and electric and/or magnetic treatments have also been confirmed to enhance seed vigor by influencing biochemical processes such as protein and enzyme activity [Moon and Chung, ]. However, these physical methods have limitations; for example, strong ultrasonic oscillation or ion beam collision might injure seed cells, thus increasing the number of destroyed seeds, and physical methods could lead to a higher possibility of a non‐uniform treatment [Goussous et al, ; Xu et al, ; Shi et al, ; Yao and Shen, ].…”
Section: Introductionmentioning
confidence: 99%
“…The theory that seed priming with SMF can alter different stages of plant growth and development has been supported by various reports. Previous studies have already confirmed the positive effects of SMF on seed germination and further phases of plant growth [Flórez et al, 2010; Shine et al, 2011; Radhakrishnan et al, 2012; Pietruszewski et al, 2013; Radhakrishnan and Ranjitha Kumari, 2013; Maffei, 2014; Jan et al, 2015; Yao and Shen, 2015; Novitskii et al, 2016; Kataria, 2017; Shine et al, 2017; Cheikh et al, 2018; Jyothi et al, 2018]. Moreover, there are some other reports indicating the supportive roles of magnetopriming on plant growth under stressful conditions through improving physiological and phytochemical characteristics [Javed et al, 2011; Anand et al, 2012; Radhakrishnan et al, 2012; Radhakrishnan and Ranjitha Kumari, 2013; Thomas et al, 2013; Roshandel and Azimian, 2015; Baghel et al, 2016, 2018, 2019; Rathod and Anand, 2016; Kataria et al, 2017; Baghel et al, 2018, 2019; Hasan et al, 2019; Kataria et al, 2019].…”
Section: Discussionmentioning
confidence: 85%
“…Yet, various reports have pointed out the effect of SMF on seed germination or further stages of plant growth [among many: Aladjadjiyan, 2002; Flórez et al, 2010; Shine et al, 2011; Pietruszewski et al, 2013; Maffei, 2014; Jan et al, 2015; Yao and Shen, 2015; Novitskii et al, 2016; Kataria, 2017; Shine et al, 2017; Cheikh et al, 2018; Jyothi et al, 2018]. In others, seed priming with electromagnetic treatment has been applied to reduce the injurious effects of abiotic stresses such as drought stress [Javed et al, 2011; Anand et al, 2012; Baghel et al, 2018; Hasan et al, 2019], salt stress [Radhakrishnan et al, 2012; Radhakrishnan and Ranjitha Kumari, 2013; Thomas et al, 2013; Baghel et al, 2016; Rathod and Anand, 2016; Baghel et al, 2019; Kataria et al, 2019], or UV stress [Kataria et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Same results with reduced MGT values where obtained for Pinus taeda L. at 150 mT for 60 minutes (Yao and Shen, 2015). In different experimental plots, in order to observe the seed morphological movements under the influence of magnetic fields, seeds where glued with non-toxic adhesive to filter paper with their long axes vertical.…”
Section: Introductionmentioning
confidence: 89%